2017
DOI: 10.1039/c7an00887b
|View full text |Cite|
|
Sign up to set email alerts
|

A novel nanozyme assay utilising the catalytic activity of silver nanoparticles and SERRS

Abstract: aArtificial enzymes have become an increasingly interesting area of research due to their many advantages over natural protein enzymes which are expensive, difficult to isolate and unable to stand harsh environments. An important area of this research involves using metal nanoparticles as artificial enzymes, known as nanozymes, which exhibit peroxidase-like activity enabling them to catalyse the oxidation of substrates such as 3,3',5,5'-tetramethylbenzidine (TMB) in the presence of hydrogen peroxide (H2O2), gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…The catalytic and enzymatic properties of NP‐based biosensing platforms have also been highlighted due to their rapid sensing process, visualization by the naked eye and high sensitivity . In particular, since MeNPs possess enzyme‐like activities, they can be utilized in the place of an enzyme in an enzyme‐linked immunosorbent assay (ELISA) to catalyze and activate the visualization reagent . Ahmed et al reported the detection of the influenza virus (H1N1) through the catalytic and enzymatic activity of a positive Au NPs ((+) Au NPs)‐based colorimetric immunoassay .…”
Section: Plasmonic and Catalytic Nanoparticle‐based Biosensing Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalytic and enzymatic properties of NP‐based biosensing platforms have also been highlighted due to their rapid sensing process, visualization by the naked eye and high sensitivity . In particular, since MeNPs possess enzyme‐like activities, they can be utilized in the place of an enzyme in an enzyme‐linked immunosorbent assay (ELISA) to catalyze and activate the visualization reagent . Ahmed et al reported the detection of the influenza virus (H1N1) through the catalytic and enzymatic activity of a positive Au NPs ((+) Au NPs)‐based colorimetric immunoassay .…”
Section: Plasmonic and Catalytic Nanoparticle‐based Biosensing Systemsmentioning
confidence: 99%
“…[52][53][54][55][56] In particular, since MeNPs possess enzyme-like activities, they can be utilized in the place of an enzyme in an enzyme-linked immunosorbent assay (ELISA) to catalyze and activate the visualization reagent. [57][58][59] Ahmed et al reported the detection of Figure 1. Target DNA sensing performance by plasmonic coupling interaction between Au NPs.…”
Section: Plasmonic and Catalytic Nanoparticle-based Biosensing Systemsmentioning
confidence: 99%
“…In this investigation, TMB (3,3 0 ,5,5 0 -tetramethylbenzidine) which is oxidized to a blue charge transfer complex (CTC) and H 2 O 2 as a substrate have been applied (Figure 4). 21 This then produces a measurable colorimetric signal which is symmetrical with the value of extant analytes. Subsequently, the concentration of the desired target has been measured by UV-Vis spectroscopy method.…”
Section: Introductionmentioning
confidence: 99%
“…[3] These advantages lead to applications such as colorimetric diagnosis, [4][5][6] electrochemical analysis, [7][8][9][10] and therapy. [11] The catalytic properties of nanozymes can be diversified by the morphology and surface of nanomaterials such as metal nanoparticles, [12,13] metal oxide nanostructures, [14][15][16] and carbon based materials. [17,18] Among these nanomaterials, cerium oxide nanoparticles (nanoceria) have recently received growing attention due to their free radical scavenging properties, which concern the coexistence of two oxidation states (Ce 3 + and Ce 4 + ) on their surface.…”
Section: Introductionmentioning
confidence: 99%